The Concept of Ta'dib Syed Muhammad Naquib al-Attas in Children's Moral Education: A Family-Based Philosophical Study - Ghina Nadia; Soleh, Achmad Khudori; Hakim, Aunul (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
Background: Islamic manners education is the main pillar in forming a child's character that is complete and dignified, especially in the midst of globalization, moral crisis, and value disorientation that has hit the modern family institution Research Objectives: This article aims to examine the concept of ta'dib according to Syed Muhammad Naquib al-Attas and its relevance in children's moral education in the family environment Methods: The method used is a literature study with a content analysis approach to relevant primary and secondary literature. Results: The results of the study indicate that: (1) ta'dib places adab as the core of Islamic education that includes spiritual, intellectual, and social dimensions holistically; (2) this concept emphasizes the close relationship between knowledge, deeds, and morals as a unity that cannot be separated in the education process; and (3) the implementation of ta'dib in the family through parental role models, the habituation of Islamic values from an early age, and the internalization of spiritual values has proven effective in forming children's characters that are honest, responsible, and civilized. Conclusions: Al-Attas' concept of ta'dib makes an important contribution to the formulation of a paradigm for children's moral education that is rooted in Islamic values and is able to respond to the challenges of the times philosophically and practically. Thus, ta'dib is not only relevant as a theoretical discourse, but also as an applied approach in family education that is oriented towards the formation of a whole person.